Robust room-temperature ferromagnetism with giant anisotropy in Nd-doped ZnO nanowire arrays - Wang, Dandan (2013)
As an important class of spintronic material, ferromagnetic oxide semiconductors are characterized with both charge and spin degrees of freedom, but they often show weak magnetism and small coercivity, which limit their applications. In this work, we synthesized Nd-doped ZnO nanowire arrays which exhibit stable room temperature ferromagnetism with a large saturation magnetic moment of 4.1 μB/Nd as well as a high coercivity of 780 Oe, indicating giant magnetic anisotropy. First-principles calculations reveal that the remarkable magnetic properties in Nd-doped ZnO nanowires can be ascribed to the intricate interplay between the spin moments and the Nd-derived orbital moments. Our complementary experimental and theoretical results suggest that these magnetic oxide nanowires obtained by the bottom-up synthesis are promising as nanoscale building blocks in spintronic devices.